Initial investigation of aerodynamic shape design optimisation for the Aegis UAV - Azabi, Yousef; Savvaris, Al; Kipouros, Timoleon (Elsevier, 2018)
This paper presents an aerodynamic design optimisation methodology used in further developing an already existing Unmanned Aerial Vehicle (UAV) platform called Aegis. This paper aims to deliver a medium altitude long endurance UAV for civilian purposes. The methodology used is also applicable to conceptual and preliminary design phases of any aerial vehicle platform. It combines a low fidelity aerodynamic analysis tool, Athena Vortex Lattice Code, with a design optimisation tool (Nimrod/O). The meta-heuristic algorithm, Multi-Objective Tabu Search-2 (MOTS2), is used to perform the optimisation process. This new methodological study optimises the UAV wing planform for level flight. It was used successfully to obtain a set of optimal wing shapes for the Aegis UAV flying at different speeds. Prior to the formulation of the design problem, a parametric study was performed to explore the design space and provide an insight into how the objective functions behave with respect to the design variables. The methodology presented here is not finalized, it is a first step to constructing a general framework that can be used to optimise the design of a twin-boom UAV aerodynamic shape. The interfacing of the already successful packages Nimrod/O, MOTS2, and AVL software produces an initial result that shows the capability of the new methodology to provide correct support decisions making for a design optimisation process that will benefit the entire community of UAV researchers and designers when it is complete.
Keywords: Multi-objective optimisation; Nimrod/O tool; Tabu search; UAV conceptual design; Parallel coordinates